Tetracyclines in Food and Feedingstuffs: From Regulation to Analytical Methods, Bacterial Resistance, and Environmental and Health Implications - Granados Chinchilla, Fabio (2017)
Antibiotics are widely used as growth promoters in animal husbandry; among them, the tetracyclines are a chemical group of relevance, due to their wide use in agriculture, surpassing in quantities applied almost every other antibiotic family. Seeing the considerable amounts of tetracyclines used worldwide, monitoring of these antibiotics is paramount. Advances must be made in the analysis of antibiotics to assess correct usage and dosage of tetracyclines in food and feedstuffs and possible residues in pertinent environmental samples. The tetracyclines are still considered a clinically relevant group of antibiotics, though dissemination of tolerance and resistance determinants have limited their use. This review focuses on four different aspects: (i) tetracyclines, usage, dosages, and regulatory issues that govern their food-related application, with particular attention to the prohibitions and restrictions that several countries have enforced in recent years by agencies from both the United States and the European Union, (ii) analytical methods for tetracyclines, determination, and residues thereof in feedstuffs and related matrices with an emphasis on the most relevant and novel techniques, including both screening and confirmatory methods, (iii) tetracycline resistance and tetracycline-resistant bacteria in feedstuff, and (iv) environmental and health risks accompanying the use of tetracyclines in animal nutrition. In the last two cases, we discuss the more relevant undesirable effects that tetracyclines exert over bacterial communities and nontarget species including unwanted effects in farmers.